Jurnalisme Damai Dalam Berita Konflik Pemain Timnas Indonesia Dan Wim Rijsbergen Pada Koran Harian Suara Merdeka - Kriskayuda, Butsiana (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2012)
Abstract: Media has important role in creating and maintaning social conductivity. However, provocative and tendencies news reporting might produce social conflict. To overcome the problem, we need alternative in gathering and writing news. The method is called peace journalism that so far became effective technique to overcome conflict. The result of the the study show that Suara Merdeka Daily Newspaper have not applied peace journalism in covering conclift between â€œTimnasâ€ and Rim Rijsbergen.Â Keywords: media, social conflict, peace journalism.